The sociological aspect of language according in Blaggat Alnisa to Aben Taiffor (280h): The discourse of woman with her husband - Al-Feredi, Alhanouf Ali; Al-Solami, AbdulLateef Marzouq (Journal of Arabic Language Sciences and Literature, 2025)
This research falls within the field of linguistics, specifically the sociology of language, also known as sociolinguistics or the sociology of linguistics. The study highlights the importance of the interaction between language and society and aims to explore and analyze the sociological and linguistic dimensions in Balāghāt al-Nisāʾ as recorded by Ibn Ṭayfūr. By employing sociolinguistic theory, the research seeks to understand various phenomena in different social contexts, such as social class distinctions, gender differences, linguistic communication elements, and communicative competencies. The study clarifies the conceptual dimensions, methodologies, and tools of sociolinguistic theory by illustrating the reciprocal relationship between language and society. It analyzes how language is used as a tool to express identity and explains linguistic differences among social groups, along with the impact of social factors such as class, gender, and geographical location. The study adopts a descriptive-analytical approach to segment and interpret texts while linking them to their surrounding social conditions. The research is limited to Balāghāt al-Nisāʾ by Ibn Ṭayfūr, particularly focusing on women’s discourse with their husbands. This selection is due to the book’s significance as one of the early Arabic sources that document women’s eloquence in refuting opponents, including figures of authority. The study aims to analyze the elements of linguistic communication, including the sender, receiver, message, code, context, and the nature of communication, to understand how women conveyed and expressed their emotions. The findings confirm that women’s discourse with their husbands aligns with sociolinguistic theory, reaffirming the strong and reciprocal relationship between language and society. Furthermore, the study emphasizes that the social nature of linguistic communication elements serves as the overarching framework within which all other linguistic components function.